Attitudes towards diversity, equity, and inclusion across the CTSA Programs: Strong but not uniform support and commitment. Issue 1 (7th February 2023) - Duong, Jeffrey; McIntosh, Scott; Attia, Jacqueline; Michener, J. Lloyd; Cottler, Linda B.; Aguilar-Gaxiola, Sergio A.
Abstract: Background: This study describes attitudes towards diversity, equity, and inclusion (DEI) among members of the Clinical and Translational Science Awards (CTSA) Program. It also explores associations between program members' roles and their perceived importance of and commitment to improving DEI and assesses the link between perceived importance of and commitment to improving DEI. Lastly, it ascertains barriers and priorities concerning health equity research, workforce development, CTSA consortium leadership, and clinical trials participation among respondents. Methods: A survey was administered to registrants of the virtual CTSA Program 2020 Fall Meeting. Respondents reported their roles, perceived importance of and commitment to improving DEI. Bivariate cross-tabulations and structural equation modeling examined associations between respondents' roles, perceived importance of DEI, and commitment to improving DEI. Grounded theory was used to code and analyze open-ended questions. Results: Among 796 registrants, 231 individuals completed the survey. DEI was "extremely important" among 72.7 percent of respondents and lowest among UL1 PIs (66.7%). Being "extremely committed" to improving DEI was reported by 56.3 percent of respondents and lowest among "other staff" (49.6%). Perceived importance of DEI was positively associated with commitment to improve DEI. Institutional and CTSA Commitment, Support, and Prioritization of DEI represented a key theme for improving DEI among respondents. Conclusion: Clinical and translational science organizations must take bold steps to transform individual perceptions of DEI into commitment and commitment into action. Institutions must set visionary objectives spanning leadership, training, research, and clinical trials research to meet the promise and benefits of a diverse NIH-supported workforce.